Pengaruh Kemudahan dan Kepercayaan Terhadap Keputusan Pembelian Pada Situs Belanja Online Lazada - Bastian Bastian; Amwar Musadad (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted to determine how much influence ease of use and trust has on purchasing decisions on the Lazada online shopping site. This research method uses quantitative methods with descriptive verification. The data collection technique used in this study was respondent data which the researchers collected as many as 384 respondents from the Lazada Instagram follower study of 3.2 million followers. This study uses path analysis to determine how much influence ease of use and trust have on purchasing decisions. The significance value of ease of use (0.000) < (0.05) and trustworthiness (0.000) < (0.05). The partial effect of ease of use on purchasing decisions is 35.5% while the variable of trust in purchasing decisions is 15.2%, individually Simultaneous total effect of ease of use and trust in purchasing decisions is 50.7% while the remaining 49.3% is influenced by other variables outside this study.